Cluster mass estimates from weak lensing - Bartelmann, Matthias (Arxiv, 1994)
The reliability of cluster lens reconstruction techniques based on weak lensing is studied in terms of the accuracy of their reproduction of the total cluster mass as a function of distance from the cluster center. To do so, a variety of reconstruction algorithms is applied to synthetic lensing data created using a sample of 60 numerically modeled clusters, and the mass reconstruction is compared to the known deflector mass. The results can be summarized as follows: (1) Reconstruction algorithms which require integrations extending over the entire real plane yield unreliable results, because they give rise to boundary effects which are hard to control; mass overestimates are more likely and more substantial in this case than underestimates. (2) Reconstruction techniques which avoid these boundary effects yield reliable lower bounds to the cluster mass. The tightness of such bounds depends on the size of the field, which can be extended synthetically to improve the results considerably. For the sample of numerical cluster models, the best lower bounds, achieved by combining synthetic field extension with non-linear, finite-field reconstruction, decline from 100% to 80% of the true cluster mass going from the cluster center to an angular distance of 2.5'. The 80% error bars of the lower mass bounds are +/- 10% to 15%.
Gesehen am 29.09.2017